Rekontekstualisasi Tradisi Tafsir Al-Qur’an di Indonesia: Mencari Kemungkinan Penggunaan Analisis Metodologis “Barat” - Kusmana Kusmana (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2002)
The effort to recontextualize Qur’anic exegesis in Indonesia—or in any other Muslim-populated region—using Western methodological approaches necessitates situating it within the broader development of Western religious studies. Over the past century, Western scholarship on religion has been dominated by historical, comparative, and phenomenological approaches, often influenced by empirical positivism and shaped by the colonial backdrop of Western scholars. This background has led to a research paradigm that positions Western culture as superior to the cultures being studied. Historically, Qur’anic studies in Indonesia have been rooted in the Islamic scholarly tradition of the Middle East, with minimal Western influence until the late 20th century. This can be attributed to Indonesia’s early exposure to Islam and its strong scholarly connections with Middle Eastern institutions. Consequently, Indonesian exegetical traditions have followed textualist approaches similar to those in the Middle East, often focusing on the text itself while overlooking the interpreter and contextual dimensions. The influence of Western scholarship on Indonesian Qur’anic studies remains limited to academic circles, with Indonesian scholars predominantly consuming rather than critically engaging with Western works. Responses to Western methodologies vary: some scholars cautiously integrate Western research, others embrace it as neutral and applicable to Islamic studies, while some advocate for a convergence of Islamic and Western epistemologies. The challenge remains in balancing academic rigor with theological commitments to foster a more dynamic and globally engaged tradition of Qur’anic exegesis in Indonesia.